AYURVEDIC GARBHA VIKAS KRAM IN CONTEXT TO EMBRYOGENESIS AND FOETAL DEVELOPMENT - D.S., Shelake; A. C, *Patil; D.V, Shukla; D.S, Meshram (International Journal of Ayurveda and Pharma Research, 2017)
Sushrut samhita is one of those Ayurvedic classic which deals with human anatomy and physiology. It gives precise description of Garbha vruddhi and vikas kram though there were no modern imaging techniques like sonography. Different Granthas state various views regarding Garbha utpatti and Garbha vriddhi. Acharyas have also mentioned Garbhini lakshana which are helpful in diagnosis of early pregnancy. Charak has mentioned signs observed in Garbhini with progression of pregnancy. Whereas modern obstetrics is one of the most cardinal branch which concerned with human reproduction. This science provide each minute detail regarding foetal growth and development. Tremendous research has been done in the field of modern obstetrics. Foetal deaths and neonatal mortality is always an issue of concern. One can get relevant references of these issues in Samhitas. Acharyas has mentioned topic of Garbha in concise form. Extensive study and discussion is essential to understand ancient concept of Garbha vikas. Review of Ayurvedic text along with modern text will help to obtain knowledge regarding this. This study is an attempt to elaborate and compare both ancient and modern concept of embryogenesis. There might be some variation when we consider both perspectives. But it is really interesting to find similarities beside a huge gap of time.